Novel mutations in ADSL for Adenylosuccinate Lyase Deficiency identified by the combination of Trio-WES and constantly updated guidelines - Xiao Mao (Nature Portfolio, 2017)
Abstract Whole-exome sequencing (WES), one of the next-generation sequencing (NGS), has become a powerful tool to identify exonic variants. Investigating causality of the sequence variants in human disease becomes an important part in NGS for the research and clinical applications. Recently, important guidelines on them have been published and will keep on updating. In our study, two Chinese families, with the clinical diagnosis of “Epilepsy”, which presented with seizures, psychomotor retardation, hypotonia and etc. features, were sequenced by Trio-WES (including the proband and the unaffected parents), and a standard interpretation of the identified variants was performed referring to the recently updated guidelines. Finally, we identified three novel mutations (c.71 C > T, p.P24L; c.1387-1389delGAG, p.E463-; c.134 G > A, p.W45*; NM_000026) in ADSL in the two Chinese families, and confirmed them as the causal variants to the disease-Adenylosuccinate Lyase Deficiency. Previous reported specific therapy was also introduced to the patients after our refined molecular diagnosis, however, the effect was very limited success. In summary, our study demonstrated the power and advantages of WES in exploring the etiology of human disease. Using the constantly updated guidelines to conduct the WES study and to interpret the sequence variants are a necessary strategy to make the molecular diagnosis and to guide the individualized treatment of human disease.